Validation of the AC[La]+EPOCfast method in sprinters and middle-distance runners - Hatauta, S.; Oki, S.; Nabekura, Y. (International Journal of Sports Medicine, 2024)
The anaerobic capacity (AC[La]+EPOCfast) method is of interest as it can differentiate between the contributions of phosphocreatine (PCr) and glycolytic energy, assess the anaerobic metabolism during a single effort, and evaluate various exercise modalities. However, no previous studies have investigated whether the superiority of the PCr and glycolytic systems can be assessed in athletes with high anaerobic capacity. This study aimed to compare the AC[La]+EPOCfast method in seven sprinters (SP) and seven middle-distance runners (MD). The participants underwent a graded exercise test and constant-load exercise at 115% VO2max until exhaustion using a bicycle ergometer. AC[La]+EPOCfast was calculated as the sum of oxygen equivalents from the phosphagen (EPCr) and glycolytic (ELa) pathways. This study reveals that there was no significant difference in AC[La]+EPOCfast or maximal accumulated oxygen deficit (MAOD) between the two groups. Although EPCr was not significantly different between groups, ELa was significantly higher in the SP group than in the MD group. In conclusion, the AC[La]+EPOCfast method can be used to evaluate high and low anaerobic capacities. However, further studies on athletes with high aerobic capacity are required.